2012
DOI: 10.3892/ol.2012.619
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of Krüppel-like factor 4 and β-catenin in human gastric cancer

Abstract: Abstract. The effects of the interaction between KLF4 and β-catenin may be significant in human carcinogenesis and tumor development. This study aimed to determine whether the expression of KLF4 and β-catenin in gastric cancer tissues is associated with clinicopathological characteristics. Western blot analysis and immunohistochemistry were performed to detect KLF4 and β-catenin expression in tumor and corresponding non-cancerous tissues from 49 patients. The data revealed that KLF4 expression was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The KLF4 protein contains both activator and repressor domains, and can function as a positive or negative regulator of gene expression [27-29]. Oncogenic effects of KLF4 have been reported in breast, skin, and lung cancers [14,15,30].…”
Section: Discussionmentioning
confidence: 99%
“…The KLF4 protein contains both activator and repressor domains, and can function as a positive or negative regulator of gene expression [27-29]. Oncogenic effects of KLF4 have been reported in breast, skin, and lung cancers [14,15,30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to screen more new biomarkers. Our recent studies have reported several molecules, such as KLF4 (Krüppel-like factor 4) (Zhang et al, 2012) and HMGA2 (high mobility group protein A2) (Zha et al, 2013), correlate with GC progression and prognosis. In present study, our data suggested that AMFR was a new candidate prognostic marker for GCs.…”
Section: Discussionmentioning
confidence: 99%
“…KLF-4 is highly expressed in adult guts (Zheng et al, 2009) and act by regulating intestinal differentiation (Li et al, 2011). Recently, the tumor suppressive role of KLF-4 has been identified in various cancers, including gastric cancer (Zhang et al, 2012), prostate cancer (Shin et al, 2014), esophageal cancer (Zhang et al, 2009), and lung cancer (Zhou et al, 2010). KLF-4 acts by deregulating the malignant transformation and cellular hyperproliferation.…”
Section: Introductionmentioning
confidence: 99%